2019
DOI: 10.1002/anie.201908289
|View full text |Cite
|
Sign up to set email alerts
|

Defect‐Rich Adhesive Nanozymes as Efficient Antibiotics for Enhanced Bacterial Inhibition

Abstract: Nanozymes have emerged as a new generation of antibiotics with exciting broad‐spectrum antimicrobial properties and negligible biotoxicities. However, their antibacterial efficacies are unsatisfactory due to their inability to trap bacteria and their low catalytic activity. Herein, we report nanozymes with rough surfaces and defect‐rich active edges. The rough surface increases bacterial adhesion and the defect‐rich edges exhibit higher intrinsic peroxidase‐like activity compared to pristine nanozymes due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
196
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(199 citation statements)
references
References 54 publications
3
196
0
Order By: Relevance
“…At day 8, the skin samples were collected from 3 mice in each group, and Spread plate culture assay was performed according to previous reports, which indicated (Figure 6b,c). [56] Moreover, ratio of wound was measured along with the period of recovery, which indicated that hollow Mn/Ni(OH) x LDHs as well as SiO 2 nanorods@Mn/Ni(OH) x LDHs, but not PBS or SiO 2 nanoparticles, fights against impaired healing process mediated by infection (Figure 6d). The result of this mice model indicated that, on the one hand, hollow Mn/Ni(OH) x LDHs alone exhibited faster wound healing compared with PBS group, suggesting that hollow Mn/Ni(OH) x LDHs structure might protect against infection in this model.…”
Section: Wound Healing Mice Model Experimentsmentioning
confidence: 95%
“…At day 8, the skin samples were collected from 3 mice in each group, and Spread plate culture assay was performed according to previous reports, which indicated (Figure 6b,c). [56] Moreover, ratio of wound was measured along with the period of recovery, which indicated that hollow Mn/Ni(OH) x LDHs as well as SiO 2 nanorods@Mn/Ni(OH) x LDHs, but not PBS or SiO 2 nanoparticles, fights against impaired healing process mediated by infection (Figure 6d). The result of this mice model indicated that, on the one hand, hollow Mn/Ni(OH) x LDHs alone exhibited faster wound healing compared with PBS group, suggesting that hollow Mn/Ni(OH) x LDHs structure might protect against infection in this model.…”
Section: Wound Healing Mice Model Experimentsmentioning
confidence: 95%
“…[2,14,15] Currently, many nanozymes with enzyme-like and antibacterial properties, including metal, carbon, and metal oxide/chalcogenide nanomaterials, have been demonstrated for killing various bacteria and even drugresistant bacteria. [4,16,17] Unfortunately, the low catalytic ability of nanozymes largely limits their antibacterial efficiency. Therefore, antibacterial nanozymes with enhanced catalytic activity is still greatly needed.…”
Section: Introductionmentioning
confidence: 99%
“…[17,21,28] However, these nanozymes mainly used NIR-I (700-900 nm) light with low maximum permissible exposure (MPE: 0.33 W cm −2 at 808 nm) and limited penetration depth, which will significantly hamper their use for in vivo applications. [17,21,22,[29][30][31][32] In comparison, NIR-II (1000-1700 nm) light has several advantages, including higher tissue penetration and higher skin-tolerance threshold (MPE: 1 W cm −2 at 1064 nm). [33,34] Therefore, antibacterial nanozymes with both catalytic activity and NIR-II photothermal property are highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Consequently, nanozymes have great potential in many fields such as environmental engineering, biological analysis, and disease diagnosis and treatment. [15][16][17][18][19] Nanozymes are a class of nanomaterials with enzyme-like properties. [4] Some nanozymes may have multi-enzyme-mimicking properties.…”
Section: Introductionmentioning
confidence: 99%